2013
DOI: 10.1155/2013/610694
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA and Cryptotanshinone Prevent Mitochondrial Dysfunction in Hypoxia-Induced H9c2 Cells: Association to Mitochondrial ROS, Intracellular Nitric Oxide, and Calcium Levels

Abstract: The protective actions of tanshinones on hypoxia-induced cell damages have been reported, although the mechanisms have not been fully elucidated. Given the importance of nitric oxide (NO) and reactive oxygen species (ROS) in regulation of cell functions, the present study investigated the effects of two major tanshinones, Tanshinone IIA (TIIA) and cryptotanshinone (CT), on hypoxia-induced myocardial cell injury and its relationships with intracellular NO and ROS, calcium, and ATP levels in H9c2 cells. Chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…Herein, we employed hypoxia to simulate the process of MI in H9c2 cells. Consistent with previous literatures [27, 28], cell viability was inhibited but cell apoptosis was promoted in H9c2 cells under persistent hypoxia. Unlike the effects of hypoxia on cancer cells [29], cell migration and invasion in H9c2 cells were both inhibited by hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…Herein, we employed hypoxia to simulate the process of MI in H9c2 cells. Consistent with previous literatures [27, 28], cell viability was inhibited but cell apoptosis was promoted in H9c2 cells under persistent hypoxia. Unlike the effects of hypoxia on cancer cells [29], cell migration and invasion in H9c2 cells were both inhibited by hypoxia.…”
Section: Discussionsupporting
confidence: 92%
“…The level of aminotransferase, an important indicator of oxidative damage, is also increased in I/R injury. 25) Many studies have reported that CT is an antioxidant being effective to cardiovascular cell damage 11,26) and carbon tetrachlorideinduced hepatic injury. 27) Similarly, in our study, the SOD activities after applying CT, were dramatically higher compared with I/R group, but the MDA content and the aminotransferase activity significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 In another study, TanIIA protected H9c2 cells via preserving mitochondrial function by reducing the excess production of mitochondrial superoxide, superoxide dismutase activity, intracellular nitric oxide, and calcium levels, and restoring cellular ATP contents. 37 In brain microvascular endothelial cells, TanIIA suppressed the expression of vascular cell adhesion molecule-1 and intercellular adhesion molecule-1 by suppressing ROS production. 38 To gain further insight into the mechanism of TanIIA on ROS reduction, we next examined the effect of TanIIA on the expression of HO-1, an important cytoprotective, anti-inflammatory, and antioxidant enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that solid dispersions of TanIIA with silica nanoparticles or low-molecular-weight chitosan achieved complete dissolution, increased the absorption rate, maintained drug stability, and showed improved oral bioavailability compared with TanIIA alone. 37,45 A study protocol for a randomized controlled trial has also been released to investigate the effect of sodium tanIIA sulfate and simvastatin on elevated serum levels of inflammatory markers in patients with coronary heart disease. 46 We believe the results in this study are noteworthy, as TanIIA can be used for the treatment of GO; further studies in humans using more developed types of TanIIA are needed to confirm these results.…”
Section: Discussionmentioning
confidence: 99%